2016
DOI: 10.4049/jimmunol.1600745
|View full text |Cite|
|
Sign up to set email alerts
|

GM-CSF Induces Inflammatory Macrophages by Regulating Glycolysis and Lipid Metabolism

Abstract: GM-CSF induces proinflammatory macrophages, but the underlying mechanisms have not been studied thus far. In this study, we investigated the mechanisms of how GM-CSF induces inflammatory macrophages. First, we observed that GM-CSF increased the extent of LPS-induced acute glycolysis in murine bone marrow-derived macrophages. This directly correlates with an inflammatory phenotype because glycolysis inhibition by 2-deoxyglucose abolished GM-CSF-mediated increase of TNF-α, IL-1β, IL-6, and IL-12p70 synthesis upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 44 publications
6
52
0
7
Order By: Relevance
“…The ability to mature and gain effector function (including the differentiation of monocytes into osteoclasts) is, however, essential for these cells. Macrophages and dendritic cells are activated in response to PAMPs and DAMPs, including TLRs, and this activation increases glycolysis to promote inflammatory function and maturation 3135 . TLR signalling through serine/threonine-protein kinase TBK1 leads to AKT activation and mTORC1 signalling to promote this glycolytic switch 3638 .…”
Section: Cellular Metabolic Reprogrammingmentioning
confidence: 99%
“…The ability to mature and gain effector function (including the differentiation of monocytes into osteoclasts) is, however, essential for these cells. Macrophages and dendritic cells are activated in response to PAMPs and DAMPs, including TLRs, and this activation increases glycolysis to promote inflammatory function and maturation 3135 . TLR signalling through serine/threonine-protein kinase TBK1 leads to AKT activation and mTORC1 signalling to promote this glycolytic switch 3638 .…”
Section: Cellular Metabolic Reprogrammingmentioning
confidence: 99%
“…production, phagocytosis and pathogen killing [68][69][70] . Pro-inflammatory T cells are known to be associated with negative disease outcome, as GM-CSF production can drive disease progression in autoimmune disorders 71 , neurological disease 72 and skin hyperinflammation 73 .…”
Section: Gm-csf Production By T Cells Activates Myeloid Cells For Infmentioning
confidence: 99%
“…For example, studies have shown that the behavior of macrophages from different tissues can be readily influenced by either altering their exposure to different metabolic substrates or by directing cells to utilize different metabolic pathways [50]. In macrophage populations outside the lung, it has been shown that cells often rely on glycolysis for driving M1 behaviors whereas M2 responses are often dependent on the use of mitochondrial respiration [50, 51]. Furthermore, M2 macrophages appear to preferentially utilize fatty acids as a substrate, which requires the use of mitochondria for β-oxidation Interestingly, recent work has demonstrated that GM-CSF itself can direct cells to utilize glycolysis, suggesting that M2 polarization in the setting of chronic alcohol exposure could be a direct consequence to the loss of GM-CSF signaling [51].…”
Section: Can Lipid Accumulation Drive Changes In Am Behavior?mentioning
confidence: 99%
“…In macrophage populations outside the lung, it has been shown that cells often rely on glycolysis for driving M1 behaviors whereas M2 responses are often dependent on the use of mitochondrial respiration [50, 51]. Furthermore, M2 macrophages appear to preferentially utilize fatty acids as a substrate, which requires the use of mitochondria for β-oxidation Interestingly, recent work has demonstrated that GM-CSF itself can direct cells to utilize glycolysis, suggesting that M2 polarization in the setting of chronic alcohol exposure could be a direct consequence to the loss of GM-CSF signaling [51]. Alternatively, it is possible that M2 polarization is just a byproduct of intracellular lipid accumulation and increased mitochondrial fatty acid β-oxidation.…”
Section: Can Lipid Accumulation Drive Changes In Am Behavior?mentioning
confidence: 99%